Preparation of hybrid CuO/TiO₂ photocatalyst responsive toward UV-Light (effect of Cu Concentration) - Azman, Nur Aifaa (2017)
The objectives of this research is to prepare hybrid CuO/TiO₂ using wet impregnation method by varying copper concentration, to characterize the photocatalyst using XRD, EDX, FESEM and BET and to evaluate the photocatalytic removal of methyl orange by hybrid CuO/TiO₂ photocatalyst. To investigate the removal efficiency of methyl orange by using hybrid CuO/TiO₂, the copper concentration was varied from 0.3 wt%, to 1.0 wt%. Results showed that 0.5 wt% CuO/TiO₂ performance was the highest with 46% removal of methyl orange. The kinetic data studies were fitted into pseudo-first, pseudo-second and intraparticle diffusion model. The kinetic of adsorption model was found to follow pseudo-first order model as the regression value at 0.5 wt% copper loading was 91%.